Factor structure validation and measurement invariance testing of the Five C's model of Positive Youth Development among emerging adults in Malaysia - Zaremohzzabieh, Zeinab; Krauss, Steven; Nouri, Katayoun Mehdinezhad (SAGE Publications, 2023)
While validation of positive youth development (PYD) measures has increased considerably of late, validation of the Five C’s of PYD among emerging adults in non-WEIRD countries remains limited. The main objective of this study was to examine the factor structure, measurement invariance, and criterion-related validity of the Five C’s model of PYD through the use of the Positive Youth Development Inventory (PYDI). Data were collected from 436 university students in Malaysia, with a mean age of 21.19 ( SD = 1.19). The findings supported a modified bifactor model of the PYDI, which demonstrated strong measurement invariance across gender and race, but not across age categories. Connection showed the strongest latent factor correlations with the other four C’s. Criterion-related validity was supported through its association with psychological hardiness. The findings demonstrate adequate psychometric properties and cultural applicability of a modified bifactor model of the Five C’s model of PYD among emerging adults in Malaysia.